Prevalência de sobrepeso e obesidade em escolares de alto nível socioeconômico em Londrina, Paraná, Brasil - Ronque, Enio Ricardo Vaz [UNESP]; Cyrino, Edilson Serpeloni; Dórea, Valfredo Ribeiro; Serassuelor Jr., Helio; Galdi, Enori Helena Gemente; De Arruda, Miguel (FapUNIFESP (SciELO), 2005)
Objective: To verify the prevalence of overweight and obesity in 7 to 10 year old schoolchildren of both sexes and high socioeconomic level. Methods: Five hundred and eleven schoolchildren (274 boys and 237 girls) were submitted to anthropometrical measurements of body mass, stature and subscapular and triceps skin-fold thickness. Body mass indexes ≥85th percentile and <95th percentile were used to determine overweight, whereas body mass indexes ≥95th percentile were adopted as indicators of obesity. The socioeconomic level was established based on information obtained from a questionnaire, considering the degree of education of the parents and the familiar consumables. Results: The total prevalence for overweight was 19.7% for the boys and 17.3% for the girls, with no significant differences amongst ages and sexes (p>0.05). On the other hand, the prevalence for obesity in the boys and girls was 17.5% and 9.3%, respectively, with significant differences between the sexes at 9 years (p<0.01) and 10 years (p<0.05) of age, as well as amongst the entire group of ages (p<0.01). Conclusion: The results indicated a high prevalence ratio for overweight (∼19%) and obesity (∼14%), much greater than the average for the 7-10 year old Brazilian population. Therefore, different from that observed in developed countries, a high socioeconomic level seems to negatively affect the prevalence for overweight and obesity, increasing the risk of the precocious development of metabolic dysfunctions.
Prevalence of overweight and obesity in schoolchildren of high socioeconomic level in Londrina, Paraná, Brazil
Keywords: Child; Food habits; Obesity; Prevalence; anthropometry; body build; body mass; Brazil; child parent relation; controlled study; education; feeding behavior; female; groups by age; human; major clinical study; male; metabolic disorder; obesity; questionnaire; school child; sex ratio; skinfold thickness; socioeconomics; statistical significance; triceps brachii muscle